Ecology and Evolutionary History of Diabrotica Beetles—Overview and Update - Astrid Eben (Insects, 2022)
An overview is given on several aspects of evolutionary history, ecology, host plant use, and pharmacophagy of Diabrotica spp. with a focus on the evolution of host plant breadth and effects of plant compounds on natural enemies used for biocontrol of pest species in the group. Recent studies on each aspect are discussed, latest publications on taxonomic grouping of Diabrotica spp., and new findings on variations in the susceptibility of corn varieties to root feeding beetle larvae are presented. The further need for in-depth research on biology and ecology of the large number of non-pest species in the genus is pointed out.